Analysis of the Status and Tendency of R&D Input in the Field of Rare Diseases Funded by the National Natural Science Foundation of China - Chang, Hanyu; Chu, Wei; Li, Xiaodan; Ma, Jing; Li, Dingguo; Yuan, Ni (Frontiers in Public Health, 2021)
Background: Through collection and sorting of rare disease projects funded by the National Natural Science Foundation of China, an understanding was gained of the categories of projects funded by the foundation in the field of rare diseases, types of diseases, categories of disease systems, regional distribution, distribution of supporting institutions, and their dynamic changes, followed by an analysis of focuses and influences of relevant state policies. This will help improve the rare disease-relating policies of the state in supporting the key fields, thus promoting healthy and sustainable development in the field of rare diseases. Method: Through the website of inquiry of projects funded by the National Natural Science Foundation of China, a retrieval was made concerning the projects funded by the foundation in the field of rare diseases during the period from 1986 to 2019, followed by descriptive analysis of fund input of rare disease projects, number of projects, temporal and regional distribution, and the analysis of the law of their dynamic changes. Result: As of the end of 2019, there were 57 rare diseases and 678 related projects funded by the National Natural Science Foundation of China, with accumulated total funding of ¥ 253,525,000. Among the categories of projects, the most-funded projects were general (¥ 150,145,000, 59.22%), followed by Youth Foundation projects (¥ 53,719,000, 21.19%) and key projects (¥ 15,870,000, 6.26%); among the categories of disease systems, the most funded disease system was the nervous system (¥ 93,186,000, 37.76%), followed by the respiratory system (¥ 35,444,000, 13.98%); the most funded diseases were multiple sclerosis (¥ 34,870,000, 13.75%), idiopathic pulmonary fibrosis (¥ 29,854,000, 11.78%), and retinitis pigmentosa (¥ 27,005,000, 10.65%); the most funded regions were East China (¥ 106,987,000, 42.20%) and North China (¥ 71,844,000, 28.34%), while the least funded region was Northwest China (¥ 7,295,000, 2.88%); among the supporting institutions, the most funded institutions were Peking University (¥ 24,720,000, 9.75%), and Sun Yat-sen University (¥ 14,505,000, 5.72%). Conclusion: With the promulgation of more policies on encouragement of innovation and accelerated approval procedures, etc., the National Natural Science Foundation of China has been increasing its funding to rare diseases, covering increasingly more categories of funded projects, more types of diseases, and wider regions. Nonetheless, the support for scientific research in China is still relatively weak. Therefore, it is proposed that the healthy and sustainable development in the course of rare diseases should be promoted through the improvement of relevant rare disease policies, encouragement of R&D of medicine for rare diseases, the establishment of special funds for rare diseases, acceleration of fund circulation, and combination of balanced development and preferential funding to key regions and major diseases.